Political Institutions and Policymaking Processes and Policy Outcomes in Mexico - Fabrice Lehoucq, Gabriel Negretto, Francisco Aparicio, Benito Nacif, Allyson Benton (My University, 2016)
This paper uses a transaction-costs framework to link the policymaking process (PMP) and the outer features of public policies in Mexico, a middle-income developing country. It shows how a highly secretive PMP, centralized around the presidency, fashioned nationalist policies that were stable, adaptable, coordinated and private-regarding for the urban-based corporatist pillars of the regime. When growth faltered in the late 1970s, however, this PMP was unable to adapt to economic volatility, although it remained dominant in an increasingly turbulent polity. The paper explains how unified government and corporatist control of the economy made a constitutionally weak president the envy of executives around the world, even at the cost of being unable to enact reforms with short-term costs for the corporatist pillars of the regime. The article also explains why democratization in the 1990s is giving rise to a less centralized and more open PMP that benefits larger shares of the population. As the separation of powers enshrined in the 1917 constitution materializes, policymaking is increasingly wedded to the status quo. On the one hand, divided government preserves a macroeconomic framework consistent with an open economy (such as fiscally sound policies and a floating exchange rate). On the other, checks and balances are helping old and new parties and interest groups to veto agreement on the raising of chronically low tax rates (at 10 percent of GDP) and on reforming nationalist policies that limit private sector investment in the state-controlled energy sector.